PENGEMBANGAN DIGITAL LEARNING KIT BERBASIS MODEL PROBLEM BASED LEARNING MATERI SISTEM PENCERNAAN DIKELAS V SD - Fardatun Nafisa; Titis Angga Rini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This development research was motivated by fifth-grade elementary school students’ limited understanding of the digestive system and the scarcity of learning materials. The results of the needs analysis indicated that students require engaging digital media to help them understand the concepts of the digestive system. This study aims to produce a PBL-based digital learning kit that is valid, practical for teachers to use, and engaging for students. The study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product consists of problem-based digital modules designed to enhance students’ motivation, enthusiasm for learning, and engagement. Data were collected through observations, interviews, and questionnaires, with a pilot test conducted at SDN Lowokwaru 5. The results showed 90.6% content validity, 100% media validity, 96.6% practicality, and 98.7% appeal. Based on these results, the PBL-based digital learning kit was deemed highly valid, practical, and suitable for use in IPAS instruction.